Physical Exercise as an Element of Cancer Recurrence Prevention - Węgrzyn, Jagoda; Gancarczyk, Maciej; Marciniak, Kinga; Ściążko-Gancarczyk, Sabina; Żukowiecka-Sęga, Dominika (Quality in Sport, 2026)
Background. Cancer recurrence represents a growing public health concern, increasingly affecting long-term survivorship and the functional well-being of individuals after oncological treatment. Emerging evidence demonstrates that structured physical activity is not only a behavioral health factor but also a modifiable component of educational and preventive programs. Exercise may influence recurrence risk through improvements in immune competence, reduction of chronic inflammation, optimization of metabolic regulation, and favorable modulation of molecular pathways associated with tumor progression. Aim. This review aims to evaluate current scientific evidence on the role of physical exercise in preventing cancer recurrence, with particular emphasis on mechanisms relevant to health promotion, behavioral change and interdisciplinary survivorship support. Review methods. Scientific literature addressing the relationship between physical exercise and cancer recurrence was identified through major biomedical databases. Studies were selected according to predefined criteria ensuring relevance and clarity, and those providing clinical, biological or psychosocial insights were included in the review.